Seasonality of admissions with multiple sclerosis in Scotland. - Handel, A; Disanto, G; Jarvis, L; McLaughlin, R; Fries, A; Ebers, G; Ramagopalan, S (2011)
BACKGROUND AND PURPOSE:   Previous studies have described a seasonal pattern of MS relapse risk. Vitamin D and infectious triggers are two major candidate environmental risk factors proposed to account for this effect. We aimed to assess MS admissions in Scotland for a possible effect of seasonality. METHODS:   Acute admissions with MS were obtained from the Scottish Morbidity Register between 1997 and 2009. We compared the pattern of these to admissions with other diagnoses. RESULTS:   We obtained data on 7098 MS and 6 243 690 non-MS acute and day-case admissions. We found a significant difference in acute MS admissions compared with admissions with other diagnoses (P = 0.0015). There was a significant excess of Scottish MS admissions in April and June with nadirs in March and October. CONCLUSIONS:   Admissions with MS show a significant seasonal variation throughout the year. Further work will be needed to identify candidate environmental factors with certainty.